CHANGES IN LUNG FUNCTION IN DIFFERENT CONDITIONS OF EQUILIBRIUM IN CLASSICAL DANCERS. (Fiep Bulletin - online, 2015)
The study "Changes in Lung Function in different conditions of Equilibrium in Classical Dancers”, aimed to analyze the influence of the processes of breathing phases in balance and support the dancer. For this research we carried out a field study was quantitative, aiming the performance of pulmonary function and quality with the purpose of improving the performance of the dancers in class and in spectacles; and the process of data collection obtained with classical dancers from two schools of the city of Bethlehem, aged 17-26 years and ballet practice time between 12 and 19 years; with the spirometer measures lung instrument were verified through Spirometry testing in the Laboratory of Exercise Physiology from the Fisioclínica/ UNAMA, in order to obtain tidal volume, expiratory reserve volume, inspiratory reserve volume, inspiratory capacity, minute volume, respiratory rate and vital capacity in different positions in the classical equilibrium conditions. He introduced us hypotheses outcomes null and alternative hypotheses, which raised questions about the existence of the air lock when the dancers dance to set up a classic pose or to continue the movement. Concluding that certain lung measures influence on breathing and performance of classical dancer. During some research questions were identified and resolved; however, the study and research in relation to the ballet is still very broad and many issues need to be questioned, tested and studied, fostering the growth of research in this area and contributing to greater acquisition and spread of knowledge.
Keywords: Classical ballerina. Breath. Balance